Developing English Supplementary Reading Cards (ESRCs) for Young Learners to Promote Free Voluntary Reading Program - Utari Praba Astuti (Jurnal Pendidikan Humaniora, 2014)
Abstract: In English classes, young learners are mostly put into intensive reading sessions as the main menu where the focus of the session is on young learners’ academic achievement. As a result, it is far from promoting reading English for pleasure. Like other skills in life, young learners learn to read by reading. The more they read, the better their reading competence will be. The better they read, the more enjoyable they find the reading activity. These paradigms function as the basis of pro-viding young learners with various reading materials to read and enough time to spend for reading. This study aimed at developing English supplementary reading material to support young learners to enjoy some reading activities. The Research and Development (R & D) procedure was employed to perform the whole process of the development and validation. With the reading material developed available, young learners are supposed to enjoy reading their own choice at their own pace as they are put into a free voluntary reading program. As a result, young learners have shifted their negative mindset about reading activity. Key Words: english supplementary reading cards, free voluntary reading program Abstrak: Dalam kelas bahasa Inggris, sebagian besar pelajar pemula dimasukkan ke dalam sesi mem-baca intensif, dengan fokus pada prestasi akademiknya. Akibatnya, jauh dari tujuan untuk mengenalkan membaca bahasa Inggris yang menyenangkan. Seperti keterampilan hidup lainnya, pelajar pemula belajar membaca bacaaan. Semakin banyak yang mereka baca, akan semakin baik kompetensi membaca mereka. Semakin baik mereka membaca, lebih menyenangkan mereka melakukan aktivitas membaca. Paradigma ini berfungsi sebagai dasar untuk menyediakan pelajar pemula dengan berbagai bahan bacaan untuk dibaca dan menyediakan waktu yang cukup untuk membaca. Penelitian ini bertujuan untuk mengembangkan bahan bacaan tambahan berbahasa Inggris untuk mendukung pelajar pemula agar menikmati kegiatan membaca. Prosedur Penelitian dan Pengembangan (R & D) dipakai untuk se-luruh proses pengembangan dan validasi. Dengan tersedianya bahan bacaan yang telah dikembang-kan, pelajar pemula seharusnya menikmati kegiatan membacanya dengan pilihan dan kemampuan mereka sendiri karena mereka dimasukkan ke dalam program membaca bebas secara sukarela. Akibat-nya pola pikir negatif mereka tentang aktivitas membaca telah bergeser.Kata kunci: kartu bacaan bahasa Inggris pelengkap, program membaca bebas dengan sukarela